Hermenêutica e a solução dos conflitos do direito - Zovico, Marcelo Luis Roland (2008)
The aim of the present work is the study of the Hermeneutics in the decision of the Conflicts of the Right, being based for in such a way, in the sociological vision of the Right for the Theory of the Systems of Niklas Luhmman. The hermeneutics has deserved deep attention of that they think the Right. To each day more, if it searchs to minimize the conflicts of the Right, glimpsing itself it necessity of one technique and a interpretativa art of the norms, capable to minimize the conflicts. Of the first chapter to third, a boarding of the historical evolution of the interpretation of the norms becomes different oldies concepts, much longer before of a complex actual society, time of interpret had another meaning, each in mythology than for who studies and then that search the concept. The social-historical progress of the world, indicates the strength its importance. Each day more, with the complex of society, became harder seek equanimous and aquilibrate and balance, specially in the normative system, fact that may cause big uncomfortableness for the society. One decision with peculation of principals, may show unbalance, awake for the needing techniques and behaviour efficacious and efficacious, contending consequent Science of Law, the sixth chapter studies the different systems of expound, passing by Ihering, Savigny, Kelsen them we get the concept of Autopoiétcs Systens and Communication, showing that the solution for the conflicts of Law is interpreting through the System Theory. At the end, in the last chapter, consider to conclude that is fundamental to reduce a complex of the societies developing instruments that get possible allow the Legal systems judge with justice